Principal Leadership, School Committee Role, and School Climate Effects on Certified Teacher Performance: Evidence from Indonesian Public Schools - Sutami, Sutami; Wijayanti, Wiwik (Journal of Innovation and Research in Primary Education, 2025)
Despite Indonesia's implementation of teacher certification programs to enhance educational quality, gaps persist between certification objectives and actual teacher performance outcomes. This study investigates the influence of organizational factors on certified teacher performance in Indonesian junior high schools. A quantitative survey was conducted among 50 certified teachers from four public junior high schools in Tanah Miring District, Merauke. Data were collected using validated questionnaires measuring principal leadership, school committee role, school climate, and teacher performance on 4-point Likert scales. Statistical analysis employed simple and multiple linear regression following classical assumption testing. All variables demonstrated high mean scores (range: 33.18-67.32). Principal leadership showed the strongest individual effect on teacher performance (β = 0.758, R² = 0.574, p < 0.001), followed by school climate (β = 0.695, R² = 0.483, p < 0.001) and school committee role (β = 0.612, R² = 0.374, p < 0.001). The simultaneous model revealed significant combined effects (F = 34.67, p < 0.001), with all three variables collectively explaining 69.5% of variance in teacher performance (adjusted R² = 0.675). In the multiple regression model, principal leadership remained the most influential predictor (β = 0.412, p < 0.001), followed by school committee role (β = 0.268, p < 0.05) and school climate (β = 0.251, p < 0.05). Principal leadership, school committee role, and school climate significantly influence certified teacher performance both individually and collectively. The findings provide a validated framework for understanding organizational factors affecting certified teacher effectiveness, with practical implications for educational management and policy development in Indonesian schools.